Effect of free stream turbulence on the topology of laminar separation bubble on a sphere. (10th October 2022) - Desai, Aditya; Mittal, Sanjay
Abstract: Abstract : The topology of a laminar separation bubble (LSB) on a sphere in the critical regime is investigated via experiments at five turbulent intensities: $T_u=0.06\, %$, $0.42\, %$, $0.71\, %$, $1.00\, %$ and $1.36\, %$ . The drag crisis occurs at a lower $Re$ and becomes gradual with increasing $T_u$ . The flow is devoid of the LSB at the onset of the critical regime. It forms on a small part of the sphere and not at all azimuthal locations, early in the critical regime. The LSB forms at more azimuthal locations with increasing $Re$ . This azimuthal expansion of the LSB is accompanied by intermittency for a small range of $Re$ . Towards the end of the critical regime, an axisymmetric LSB forms on the sphere at all time instants. A model is proposed to estimate the azimuthal extent and distribution of the LSB from the mean force coefficients of a flow state. The model predicts that the LSB forms as multiple segments for a large part of the critical regime. During the spatial growth of the LSB with $Re$ in the critical regime, some of its fragments relocate to alternate locations. Moderate increase in $T_u$ ( $0.42\, % ≤ T_u ≤ 0.71\, %$ ) leads to rich dynamics with several intermittent flow states. However, fewer intermittent states are observed beyond a certain $T_u$ ( ${≥ }1.00\, %$ ).